Asymmetric vinylogous mannich reaction of silyloxy furans with N-tert-butanesulfinyl ketimines - Rao, V. U. Bhaskara; Jadhav, Amol P.; Garad, Dnyaneshwar N.; Singh, Ravi P. (Organic Letter, 2014)
A highly regio- and diastereoselective TMSOTf promoted vinylogous Mannich reaction for the synthesis of chiral quaternary 3-aminooxindole butenolides from 2-silyloxy furans and chiral ketimines is described. The method is found to be very efficient and also provides a facile access to sterically challenging 3-aminooxindole butenolides bearing two quaternary centers in continuation. Further, the versatility of the method is demonstrated by the 1,4-addition of nucleophiles on the sterically congested butenolide substructure..

Asymmetric vinylogous michael reaction of cyclic enones with silyloxy furans - Jadhav, Amol P.; Rao, V. U. Bhaskara; Singh, Pradeep; Gonnade, Rajesh G.; Singh, Ravi P. (Chemical Communications, 2015)
The asymmetric vinylogous Michael reaction of cyclohexenone/medium and large cyclic enones with 2-silyloxyfuran is still a synthetic challenge. In this report, we have explored 1,4-conjugate addition of an enantioselective chiral, primary diamine catalyzed, 2-silyloxy furan to various cyclic enones and beta-substituted cyclic enones. The reaction provided syn-Michael adducts (cycloalkane connected gamma-butenolide) with good yields, diastereo and enantioselectivities. Furthermore, the synthetic potential of these syn-Michael adducts is demonstrated by 1,4-addition of nucleophiles on the butenolide substructure.

Intramolecular dehydrogenative coupling of 2,3-diaryl acrylic compounds: access to substituted phenanthrenes - Gupta, Vijay; Rao, V. U. Bhaskara; Das, Tamal; Vanka, Kumar; Singh, Ravi P. (Journal of Organic Chemistry, 2016)
A simple, facile, and environmentally benign intramolecular dehydrogenative coupling of various 1,2-diarylethylenes for the synthesis of phenanthrenes in excellent yield has been described. This new methodology uses ceric ammonium nitrate (CAN) as a promoter at room temperature and has been extended to intermolecular synthesis of biaryl compounds. The electron transfer from methoxyarene to cerium leads to cationic radical formation, which further proceeds to intramolecular coupling. Preliminary mechanistic investigation by EPR spectroscopy and density functional theory calculation suggested a similar view.

DBU-mediated diastereoselective aldol-type cyanomethylation of isatins - Rao, V. U. Bhaskara; Kumar, Krishna; Das, Tamal; Vanka, Kumar (Journal of Organic Chemistry, 2017)
An efficient, metal-free approach to 3-substituted 3-hydroxybxindole by DBU-mediated highly diastereoselective addition of aryl acetonitrile to N-protected isatin under mild conditions has been developed. The reaction proceeds smoothly to produce respective cyanomethylated adducts in good yield and excellent diastereoselectivity. Further transformation of the cyanide group allowed the synthesis of an advance intermediate of corresponding (+/-) CPC analogue. The mechanistic insight :toward the aldol-type cyanomethylation, of N-tritylisatin with benzyl cyanide was obtained by DFT calculations.